Efficiency of Some Bacterial Strains in Potassium Release from Mica and Phosphate Solubilization under In Vitro Conditions. Issue 9 (20th October 2016) - Sarikhani, Mohammad R.; Khoshru, Bahman; Oustan, Shahin
ABSTRACT: Phosphorus and potassium (K) are major essential macronutrients for biological growth and development. Application of beneficial microorganisms to soil is one approach to enhance crop growth. In this study, the ability of five bacterial strains, including four strains of Pseudomonas sp. (S10-3, S14-3, S19-1, and S21-1) and one strain of Azotobacter sp. SP16, to release K from muscovite and biotite was investigated. Furthermore, phosphate solubilization by these strains was measured when an insoluble source of P [Ca3 (PO4 )2 ] was added to the medium. Among the bacterial strains, the highest average K release (73% higher than control) was observed with Pseudomonas sp. S14-3. The average amount of K released from biotite was 37% higher than that from muscovite in inoculated treatments. The enhanced release of mineral K might be attributed to the release of organic acids from the bacteria, a mechanism which plays a pivotal role in solubilizing phosphate from inorganic sources. The results confirmed the enhanced phosphate solubilization by the bacterial strains in the presence of muscovite. The highest P solubilizing activity (67% higher than control) was found in S21-1 and S14-3 strains. Concentrations of both K and P in the liquid phase were increased by increasing the time of experiment. X-ray diffraction analysis of muscovite specimens inoculated with S14-3 strain revealed a partial transformation of these minerals through the presence of 19.5 Å peak on the diffractogram of the magnesium-saturated sample. This may be due to the release of K from the interlayer space and subsequent filling with a number of bacterial metabolites. The findings of this research suggest K depletion from mica in the presence of bacteria, but further investigations are needed to clarify the mechanisms involved.